The Norwegian vocational college: heterogenous aggregate of intermediate educations, or a parallel pillar to higher academic education? - Høst, Hakon [Verfasser]; Michelsen, Svein [Verfasser] (My University, 2021)
“For long the Norwegian vocational college was placed in the periphery of general system formation policies in education and remained a residual in technical education, based on praxis values and local support from industry. In 2003 the vocational college was extended to cover a wide range of institutions and programs and defined as a separate level in the educational structure. Recently, through the turn towards labour market relevance in education, the vocational colleges have experienced considerable political attention as well as increased public financing. Under their new name, higher vocational education, the colleges are now intended to provide employees without higher, academic education, with a stronger foothold in the labour market. Previous policy decisions on limiting the vocational college to level 5 in the national qualification framework are now being reconsidered. Organizational rationalization processes have furthermore strengthened the capabilities of the schools to engage in higher education programs. These developments may provide a new basis for the development of a practical higher educational pillar parallel to academic higher educational.).” (authors’ abstract; BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2.1 Westeuropa; 370; Berufsbildungssystem; Berufsschule; Höhere Berufsbildung; Nationaler Qualifikationsrahmen; Norwegen